BENCHMARKING METODE RANCANG BANGUN WATERFALL DAN PEMODELAN BERBASIS OBJEK - Moch. Khusien Bagaskoro; M. Amirul Chakim; Mohammad Nurul Hilal; One Thowimma (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2021)
This research is a research Benchmarking Waterfall Design Method and Object-Based Modeling. Software development has many models, software methodologies have evolved from time to time, including the Waterfall approach and the UML (Unified Modeling Language) approach. Waterfall is a software development model that is carried out sequentially and very systematically. Meanwhile, UML is a visual modeling method that serves as a means of designing object-oriented systems. The difference between the two models is that Waterfall is a structured method, while UML is a system analysis method, a representation of the programming method. This study aims to perform a comparison or benchmarking of each of these software models, which can assist in determining the most suitable model for the current software development process. The method used in this research is descriptive quantitative method, which analyzes data by describing or describing the data that has been collected as it is. From the results of this study, it can be concluded that the UML method is most suitable for software development, because UML in terms of development, is a method that has undergone evolution from previous methods, so this method can follow the use of users in designing projects on a medium to large scale. That are relevant to the current developments